Beyond (+) and (-): Investigating prospective elementary school teachers’ misconceptions in mathematical operations - Ardiansari, Lia; Siagian, Muhammad Daut (Journal of Didactic Mathematics, 2025)
This study investigates prospective elementary school teachers' misconceptions of the (+) and (?) symbols by exploring their perceptions in various mathematical contexts. The aim is to understand how students interpret these fundamental operations and identify potential challenges in their conceptualization. Since teachers’ understanding of mathematical symbols plays a crucial role in shaping students’ learning experiences, it is essential to uncover gaps between their conceptual and procedural knowledge. This study involved 65 undergraduate students majoring in elementary teacher education, selected to ensure a diverse range of academic backgrounds and experiences. Data were collected through written assessments and semi-structured interviews, then analyzed thematically to identify recurring misconceptions. The findings indicate that while students demonstrate procedural fluency in basic arithmetic, significant misunderstandings arise when dealing with negative numbers, inverse operations, and algebraic expressions. Many students perceive the minus sign solely as an operator rather than a representation of a negative value, leading to difficulties in interpreting mathematical expressions in different contexts. These results highlight the need for instructional approaches that emphasize conceptual understanding alongside procedural skills. The study contributes to mathematics education research by providing insights into how prospective teachers interpret mathematical symbols and offering recommendations for improving teacher preparation programs.